High flow from Impella 5.5 with partial veno‐arterial extracorporeal membrane oxygenation support: Case series. Issue 6 (2nd February 2022) - Ohira, Suguru; Pan, Stephen; Levine, Avi; Haidry, Syed A.; Aggawal‐Gupta, Chhaya; Lanier, Gregg; Gass, Alan; De La Pena, Corazon; Goldberg, Joshua B.; Spielvogel, David; Kai, Masashi
Abstract: Optimal flow balance between Impella 5.5 and veno‐arterial extracorporeal membrane oxygenation (ECMO) support in the setting of EC‐PELLA (ECMO+Impella) is unknown. Outcomes of high Impella 5.5 flow in the setting of EC‐PELLA support were reviewed ( N = 7). EC‐PELLA was successfully explanted in 6 patients (bridge‐to‐transplant, N = 1; bridge‐to‐recovery, N = 5). The median duration of EC‐PELLA support in explanted patients was 6 days. Survival at discharge was 71.4% (5 patients). In terms of device‐related events, either VA‐ECMO or Impella‐related complications were not experienced. The median performance level of Impella 5.5 was P5 at the time of starting EC‐PELLA support and then increased with time up to the median of P8 with increment of the Impella flow, and index (L/min/m 2 ). The percentage of Impella flow per total EC‐ PELLA flow reached 50% after 48 h of support. The vasoactive‐inotropic score and serum lactate level improved after institution of EC‐PELLA support as well as the pulmonary artery pressures and central venous pressure. In conclusion, a high pump flow from Impella 5.5 with partial VA‐ECMO support in the setting of EC‐PELLA provided great support with favorable survival and device‐related complications rate.